The Montgolfier Brothers and the Invention of Aviation 1783-1784 : With a Word on the Importance of Ballooning for the Science of Heat and the Art of Building Railroads - Gillispie, Charles Coulston (Book collections on Project MUSE., 1983)
This vividly illustrated book introduces the reader to the brothers Montgolfier, who launched the first hotair balloon in Annonay, France on 4 June 1783. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.